Penyuluhan Program Pembinaan Kesehatan Kerja pada Pembudidaya Rumput Laut Kampung Beru Takalar - Salam, Jumhur; Hamid, Fatmawati; Arsastha, Liang Kevin; Wenas, Asterlita Ryane (-, 2025)
Occupational diseases represent a significant burden on both health and the economy, as they not only require healthcare services and associated costs but also decrease worker productivity. One of the most common occupational diseases is contact dermatitis, particularly among seaweed farmers. This community service initiative aims to provide seaweed farmers in Beru Village, Takalar with education about the Occupational Health Program. The outreach was conducted through lectures and presentations using PowerPoint as a medium. The content covered the importance of occupational health, risk management, and the proper implementation of safety procedures in seaweed cultivation activities. The objective of this activity is to enhance the community's understanding of the importance of maintaining occupational health to prevent potential diseases or injuries related to their work. The expected outcome of this activity is to raise awareness among seaweed farmers about the significance of occupational health and reduce the health risks that may arise in the field. After the presentation, participants were allowed to ask questions and engage in discussions related to the material.